Language Learning Strategies: A Case of Indonesian Students Studying in the United Kingdom - Indah, Nopita Nurpa; Yunita, Wisma; Maisarah, Ira (Journal of English Education and Teaching, 2023)
This study aimed to find out the language learning strategies used by Indonesian students during their studies at the University of Leeds in the United Kingdom, the obstacles faced in implementing the learning strategy, and how to overcome the obstacles in implementing the learning strategy. Data obtained by providing a questionnaire and interview. The questionnaire was adopted from the Oxford theory, which consists of 50 statements with five answer choices in the form of Google form to 30 Indonesian students who studied at the University of Leeds. Then, the writer conducted the interview via zoom meeting that focused on the participants’ reasons and experiences with the language learning strategies they used. The result showed that: (1) the Indonesian students studying at the University of Leeds dominantly used cognitive, metacognitive, and social strategies. (2) The Indonesian students faced some obstacles in implementing the learning strategy, and they came from two factors: internal (study habits and study concentration) and external (teacher teaching style and the social environment). (3) The Indonesian students overcome those obstacles by applying different kinds of learning strategies. These findings relate to the importance and the use of language learning strategies for students who want to continue their studies overseas. Keywords: Language Learning Strategies; Indonesian Student; United Kingdom.